At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Let's go through the solution step-by-step.
### Given:
The circle \( L \) with equation \( x^2 + y^2 = 9 \).
Point \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) is on the circle.
### Part (a) - The gradient of \( OP \):
The gradient of a line passing through points \( O(0, 0) \) and \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) is calculated as follows:
[tex]\[ \text{Gradient of } OP = \frac{y_2 - y_1}{x_2 - x_1} = \frac{\frac{3\sqrt{3}}{4} - 0}{\frac{3}{2} - 0} = \frac{\frac{3\sqrt{3}}{4}}{\frac{3}{2}} \][/tex]
Simplifying the fraction:
[tex]\[ = \frac{3\sqrt{3}}{4} \div \frac{3}{2} = \frac{3\sqrt{3}}{4} \times \frac{2}{3} = \frac{3\sqrt{3} \cdot 2}{3 \cdot 4} = \frac{6\sqrt{3}}{12} = \frac{\sqrt{3}}{2} \][/tex]
So, \( \frac{\sqrt{3}}{a} = \frac{\sqrt{3}}{2} \). Therefore,
[tex]\[ a = 2 \][/tex]
### Part (b) - The gradient of the tangent at \( P \):
The gradient of the tangent to a circle at any point is the negative reciprocal of the gradient of the radius to that point.
The gradient of the tangent at \( P \):
[tex]\[ \text{Gradient of the tangent} = -\frac{1}{\text{Gradient of } OP} = -\frac{1}{\frac{\sqrt{3}}{2}} = -\frac{2}{\sqrt{3}} \][/tex]
So, \( \frac{b}{\sqrt{3}} = -\frac{2}{\sqrt{3}} \). Therefore,
[tex]\[ b = -2 \][/tex]
### Part (c) - The equation of the tangent and where it intersects the \( y \)-axis:
The equation of the tangent to the circle at point \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) with a gradient of \( -\frac{2}{\sqrt{3}} \) is:
Using the point-slope form \( y - y_1 = m (x - x_1) \):
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \left( x - \frac{3}{2} \right) \][/tex]
To find the \( y \)-intercept where \( x = 0 \):
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \left( 0 - \frac{3}{2} \right) \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \times -\frac{3}{2} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \frac{6}{2\sqrt{3}} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \frac{3\sqrt{3}}{3} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \sqrt{3} \][/tex]
[tex]\[ y = \sqrt{3} + \frac{3\sqrt{3}}{4} \][/tex]
[tex]\[ y = \frac{4\sqrt{3}}{4} + \frac{3\sqrt{3}}{4} \][/tex]
[tex]\[ y = \frac{7\sqrt{3}}{4} \][/tex]
So, the \( y \)-intercept is \( \left( 0, \frac{7\sqrt{3}}{c} \right) \).
Therefore,
[tex]\[ \frac{7\sqrt{3}}{c} = \frac{7\sqrt{3}}{4} \][/tex]
[tex]\[ c = 4 \][/tex]
### Conclusion:
- (a) \( a = 2 \)
- (b) \( b = -2 \)
- (c) [tex]\( c = 4 \)[/tex]
### Given:
The circle \( L \) with equation \( x^2 + y^2 = 9 \).
Point \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) is on the circle.
### Part (a) - The gradient of \( OP \):
The gradient of a line passing through points \( O(0, 0) \) and \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) is calculated as follows:
[tex]\[ \text{Gradient of } OP = \frac{y_2 - y_1}{x_2 - x_1} = \frac{\frac{3\sqrt{3}}{4} - 0}{\frac{3}{2} - 0} = \frac{\frac{3\sqrt{3}}{4}}{\frac{3}{2}} \][/tex]
Simplifying the fraction:
[tex]\[ = \frac{3\sqrt{3}}{4} \div \frac{3}{2} = \frac{3\sqrt{3}}{4} \times \frac{2}{3} = \frac{3\sqrt{3} \cdot 2}{3 \cdot 4} = \frac{6\sqrt{3}}{12} = \frac{\sqrt{3}}{2} \][/tex]
So, \( \frac{\sqrt{3}}{a} = \frac{\sqrt{3}}{2} \). Therefore,
[tex]\[ a = 2 \][/tex]
### Part (b) - The gradient of the tangent at \( P \):
The gradient of the tangent to a circle at any point is the negative reciprocal of the gradient of the radius to that point.
The gradient of the tangent at \( P \):
[tex]\[ \text{Gradient of the tangent} = -\frac{1}{\text{Gradient of } OP} = -\frac{1}{\frac{\sqrt{3}}{2}} = -\frac{2}{\sqrt{3}} \][/tex]
So, \( \frac{b}{\sqrt{3}} = -\frac{2}{\sqrt{3}} \). Therefore,
[tex]\[ b = -2 \][/tex]
### Part (c) - The equation of the tangent and where it intersects the \( y \)-axis:
The equation of the tangent to the circle at point \( P \left( \frac{3}{2}, \frac{3\sqrt{3}}{4} \right) \) with a gradient of \( -\frac{2}{\sqrt{3}} \) is:
Using the point-slope form \( y - y_1 = m (x - x_1) \):
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \left( x - \frac{3}{2} \right) \][/tex]
To find the \( y \)-intercept where \( x = 0 \):
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \left( 0 - \frac{3}{2} \right) \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = -\frac{2}{\sqrt{3}} \times -\frac{3}{2} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \frac{6}{2\sqrt{3}} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \frac{3\sqrt{3}}{3} \][/tex]
[tex]\[ y - \frac{3\sqrt{3}}{4} = \sqrt{3} \][/tex]
[tex]\[ y = \sqrt{3} + \frac{3\sqrt{3}}{4} \][/tex]
[tex]\[ y = \frac{4\sqrt{3}}{4} + \frac{3\sqrt{3}}{4} \][/tex]
[tex]\[ y = \frac{7\sqrt{3}}{4} \][/tex]
So, the \( y \)-intercept is \( \left( 0, \frac{7\sqrt{3}}{c} \right) \).
Therefore,
[tex]\[ \frac{7\sqrt{3}}{c} = \frac{7\sqrt{3}}{4} \][/tex]
[tex]\[ c = 4 \][/tex]
### Conclusion:
- (a) \( a = 2 \)
- (b) \( b = -2 \)
- (c) [tex]\( c = 4 \)[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.